Definitive Hematopoietic Multipotent Progenitor Cells Are Transiently Generated From Hemogenic Endothelial Cells in Human Pluripotent Stem Cells. Issue 5 (14th October 2015) - Bai, Hao; Liu, Yanfeng; Xie, Yinliang; Hoyle, Dixie L.; Brodsky, Robert A.; Cheng, Linzhao; Cheng, Tao; Wang, Zack Z.
Abstract : Generation of fully functional hematopoietic multipotent progenitor (MPP) cells from human pluripotent stem cells (hPSCs) has a great therapeutic potential to provide an unlimited cell source for treatment of hematological disorders. We previously demonstrated that CD34 + CD31 + CD144 + population derived from hPSCs contain hemato‐endothelial progenitors (HEPs) that give rise to hematopoietic and endothelial cells. Here, we report a differentiation system to generate definitive hematopoietic MPP cells from HEPs via endothelial monolayer. In the presence of angiogenic factors, HEPs formed an endothelial monolayer, from which hematopoietic clusters emerged through the process of endothelial‐to‐hematopoietic transition (EHT). EHT was significantly enhanced by hematopoietic growth factors. The definitive MPP cells generated from endothelial monolayer were capable of forming multilineage hematopoietic colonies, giving rise to T lymphoid cells, and differentiating into enucleated erythrocytes. Emergence of hematopoietic cells from endothelial monolayer occurred transiently. Hematopoietic potential was lost during prolonged culture of HEPs in endothelial growth conditions. Our study demonstrated that CD34 + CD31 + CD144 + HEPs gave rise to hematopoietic MPP cells via hemogenic endothelial cells that exist transiently. The established differentiation system provides a platform for future investigation of regulatory factors involved in de novo generation of hematopoietic MPP cells and their applications in transplantation. J. Cell. Physiol. 231: 1065–1076, 2016. © 2015 Wiley Periodicals, Inc.